Development of econometric models for assessing the impact of investment investments into the industry on profit - Hojiqulova Feruza Dona qizi; Khatamov Ochildi Kurbanovich (THE INNOVATION ECONOMY, 2026)
The article discusses the development of econometric models for assessing the impact of investments in the industrial sector on GRP in our region. These models study how investments in the industrial sector are linked to GRP and production efficiency. As a result, they help determine the impact of investments on economic develop ment and develop effective policy strategies.